Kulturowy aspekt przemian rynku usług - Rembowska, Krystyna (Space – Society – Economy, 2008)
We are now witnessing and taking part in the process of changing industrial society into postindustrial society. The culture as a lifestyle has become a key factor in a new community. To understand the idea and the social meaning of contemporary socio-spacial changes there must be an attempt to describe the real values of postindustrial society changes. The presented way of analysis has been applied to service market which represents the pace of civilization changes. Development and functioning of services are under the influence of: commercialization of services, consumerism, and growing importance of information. Abundance, accumulation, and multitude of goods and services are some of the most striking characteristics of modern circulation of goods and services. The above directions of service sector changes in contemporary societies exemplify the cultural influence on them.